Pengelolaan Pendidikan Literasi Media di Pondok Pesantren WALI Salatiga - Aeni, Nurul; Fakhruddin, Fakhruddin (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2020)
The objective of this research was to describe the program management of media literacy education and explain inhibiting and supporting factors of Media Literacy Education in Islamic Boarding School WALI Salatiga. This research used qualitative approach. The data were collected by using observation, interview and documentation. The sample used in this research involved one Islamic boarding school’s tutor, one cleric, one manager and three students. Data validity techniques used is triangulation of sources and methods. Data analysis technique used are data collection, data reduction, data presentation, and drawing conclusions. The results of this research showed that: The research results obtained that program management of Media Literacy Education in Islamic Boarding School WALI Salatiga begins from planning, implementation, and ends with evaluation. In addition, there are factors that influence the management process, namely, inhibiting factors; students’ awareness that does not always come or students sometimes come (student’s internal motivation) and lack of infrastructure. Supporting factors are clerics who are competent in their fields, coaching and learning strategies that are fun.